Pediatric Non-Alcoholic Fatty Liver Disease Is Affected by Genetic Variants Involved in Lifespan/Healthspan - Crudele, Annalisa; Dato, Serena; Re, Oriana Lo; Maugeri, Andrea; Sanna, Paola; Giallongo, Sebastiano; Oben, Jude; Panera, Nadia; De Rango, Francesco; Mosca, Antonella; Rose, Giuseppina; Passarino, Giuseppe; et al. (Journal of pediatric gastroenterology and nutrition, 2021)
OBJECTIVES: Non-alcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver disease in both adults and children. Along with obesity and metabolic syndrome, genetic predisposition influences the progression of NAFLD. Here, we investigated the effect of lifespan/healthspan-related single nucleotide polymorphisms (SNPs) on metabolically associated fatty liver disease in children. METHODS: We evaluated the impact of 10 SNPs involved in both human liver/metabolic diseases and healthspan (interleukin-6 [IL-6] rs1800795, antisense non coding RNA in the INK4 locus (ANRIL) rs1556516, SH2B3/ATXN2 rs7137828, FURIN rs17514846, TP53 rs1042522, APOC3 rs2542052, KL rs9536314, KL rs9527025, SIRT6 rs107251, FOXO3 rs2802292) on NAFLD-related metabolic and liver features in 177 pediatric patients with biopsy-proven NAFLD, by comparing them to 146 healthy controls. We then applied a multidimensional reduction (MDR) case-control analysis of SNP-SNP interactions, to identify the joint effect of analyzed SNPs in predicting NAFLD and associated features. RESULTS: Discrete SNPs were significantly associated with individual metabolic NAFLD features, but none of them significantly associated with NAFLD diagnosis. By testing potential synergies using the MDR approach, the best combination to diagnose NAFLD (P = 0.0011) resulted in the one encompassing IL-6 rs1800795 and ANRIL rs1556516. Consistently, the risk combinations suggested by SNP-SNP analysis strongly associated with a higher level of fasting plasma blood glucose level (P = 0.024). CONCLUSION: In conclusion, here we demonstrated a synergic interaction between IL-6 rs1800795 and ANRIL rs1556516 in the diagnosis of NAFLD, and NAFLD-associated hyperglycemia in children. Larger studies are required to confirm our findings and to elucidate mechanisms by which the genetic interaction between these two genes influences healthspan in pediatric NAFLD.
Keywords: Child; játra; jednonukleotidový polymorfismus; Longevity; Adult; dospělí; Polymorphism, Single Nucleotide; Genetic Predisposition to Disease; Humans; Liver; lidé; Sirtuins; Non-alcoholic Fatty Liver Disease; sirtuiny; dítě; genetická predispozice k nemoci; nealkoholová steatóza jater; dlouhověkost